Whole-genome duplication leads to significant but inconsistent changes in climatic niche - Patrick G. Meirmans; Filip Kolář (Proceedings of the National Academy of Sciences, 2025)
Polyploidization (whole-genome duplication, WGD) is a widespread large-effect macromutation with far-reaching genomic, phenotypic, and evolutionary consequences. Yet, we do not know whether the consistent phenotypic changes that are associated with polyploidization translate into predictable changes in ecological preferences. Niche modeling studies in mixed-ploidy species provide an opportunity to compare recently originated polyploids with their lower-ploidy ancestors. However, the available isolated studies provide contrasting results and the diverse methodologies used limit generalization. Based on 25,857 georeferenced ploidy-verified occurrence data for 129 mixed-ploidy flowering plant species, we tested in a unified statistical framework whether WGD is associated with consistent changes in climatic niche and in past, current, and predicted future range size. We found that 74% of species exhibited significant niche shifts associated with ploidy transition. However, there was no consistent environmental parameter underlying ploidy differentiation across species, nor was there consistent support for polyploid range or niche expansion in a subset of 75 densely sampled species with sufficient data for modeling. Our results demonstrate that polyploidization is an important factor affecting niche evolution of a species, but the environmental parameters underlying the ploidy-related niche shifts vary from species to species, demonstrating limited predictability of the outcomes of WGD in ecological space.